2019
DOI: 10.2147/dddt.s215337
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of loratadine, a histamine H<sub>1</sub> receptor antagonist, on the skeletal system of young male rats</p>

Abstract: BackgroundHistamine H1 receptor antagonists are widely used in the treatment of allergic diseases. H1 receptors are expressed on bone cells and histamine takes part in regulation of bone metabolism. Loratadine is often prescribed to children.PurposeThe aim of the present study was to investigate the effects of loratadine on the skeletal system of young rats.Material and methodsLoratadine (0.5, 5, and 50 mg/kg p.o. daily) was administered for 4 weeks to male Wistar rats, 6-week-old at the start of the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Rats are very often used as the animal experimental model for the assessment of the impact of drugs on the male reproductive system [ 40 42 ], bones [ 43 , 44 ], and as well as for the evaluation of direct tissue toxicity [ 45 , 46 ]. Laboratory methods and reagents are available for measurements of hormone levels and immunological studies in rats, ensuring repeatability and facilitating the comparison of results.…”
Section: Introductionmentioning
confidence: 99%
“…Rats are very often used as the animal experimental model for the assessment of the impact of drugs on the male reproductive system [ 40 42 ], bones [ 43 , 44 ], and as well as for the evaluation of direct tissue toxicity [ 45 , 46 ]. Laboratory methods and reagents are available for measurements of hormone levels and immunological studies in rats, ensuring repeatability and facilitating the comparison of results.…”
Section: Introductionmentioning
confidence: 99%
“…The high dose of 50 mg/kg, however, significantly affected the longitudinal bone growth and cancellous bone mineralization, while no other effects on the skeletal system were observed. Due to a decreased body mass gain and increased liver mass, this effect might have been attributed to toxicity, and not only to loratadine's effect on H1-receptors [20]. It seems that cetirizine and loratadine can affect bone growth and structure of the bone in higher dosages, while lower dosages seem to have no significant influence.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, cetirizine did not affect bone mineral density or bone quality in a study investigating osteoporotic phenotype and wild type mice [4]. Another study investigated loratadine, which is a second generation H1-antihistamine-like cetirizine, and its effect on the skeletal system of rats [20]. A high dose of loratadine slightly, but significantly, affected the development of the skeletal system in rapidly growing rats [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loratadine a H1 receptor antagonist slightly favorably affect mechanical properties of compact bone [55]. Furthermore loratadine, often prescribed to allergic children, is able to slightly but significantly affect at high dose the development of the skeletal system in rapidly growing rats [56]. However, Aasarød et al found increased levels of histamine in an animal model of gastric hypoacidity and hypergastrinemia associated with reduced bone quality and mechanical bone strength while the H1R antagonist cetirizine did not show to be beneficial on bone parameters [57][58][59][60].…”
Section: Histaminementioning
confidence: 99%